Drug-resistant bacterial pathogens in milk and some milk products. Issue 3 (6th May 2014) - Marjan, Shajuty; Kanta Das, Kamal; Kishore Munshi, Saurab; Noor, Rashed
Abstract : Purpose: – Current study was carried to detect the presence of pathogenic bacteria including the drug-resistant ones from milk and milk products. The paper aims to discuss these issues. Design/methodology/approach: – Twenty-six raw milk samples from ten different areas, 28 pasteurized milk samples from 12 different companies and 26 yogurt samples from ten different sources in Dhaka city were microbiologically analyzed through cultural and biochemical identification of the isolates. Drug resistance trait was also determined by the Kirby-Bauer method on Muller-Hinton agar. Findings: – Out of 80 samples studied, 74 were found to harbor pathogens within a range of 102-104 cfu/ml, including Escherichia coli, Salmonella spp., Staphylococcus aureus, and Vibrio spp. The study of antibiogram revealed that most of the isolates were resistant against most of the commonly used antibiotics. Research limitations/implications: – Employment of only cultural/ biochemical tests excluding the molecular detection of virulence and/or antibiotic resistance genes might stand as a shortfall of the study. Nevertheless, such basic approach of microbiology can make this type of study replicable in the resource poor settings in the other developing countries. Practical implications: – Routine detection of drug-resistant bacteria can further unveil the complications in chemotherapy during the endemic food borne diseases. Social implications: – The study outcome/knowledge would aid to a better public health management especially in the developing countries. Originality/value: – The presence of drug-resistant pathogenic bacteria in most of the tested milk samples poses a great public health threat, especially to the children. Therefore, the study revealed the necessity of maintaining proper hygienic practice and care in handling and processing of milk and milk products.